STRUKTUR DAN UNSUR KEBAHASAAN TEKS EKSPLANASI SISWA KELAS XI SMA NEGERI 2 BATANG ANAI - Sukayati, Sukayati; Pramesti, Utami Dewi (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
ABSTRACT The Purpose of this study were.  (1)to describe the use of explanatory the text structure of the student of class XI SMA Negeri 2 Batang Anai. (2) to describe the use of linguistic element in explanatory the text of the strudent of class XI SMA Negeri 2 Batang Anai. (3) to describe accuracy of element and structure of the explanatory text of the student of class XI SMA Negeri 2 Batang Anai. This type of research is qualitative using descriptive methods. Data from this study are the structure and linguistic element of the explanatory text. The data source used in this study a document. The document used is a collection of explanatory text of the student of class XI SMA Negeri 2 Batang Anai. The instrument in this study was the researcher himself. Kata kunci: Struktur, Unsur Kebahasaan, Teks Eksplanasi